2021
DOI: 10.3389/fmicb.2021.630814
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recombinant Protein Production Under Special Environmental Stress

Abstract: Regardless of bacteria or eukaryotic microorganism hosts, improving their ability to express heterologous proteins is always a goal worthy of elaborate study. In addition to traditional methods including intracellular synthesis process regulation and extracellular environment optimization, some special or extreme conditions can also be employed to create an enhancing effect on heterologous protein production. In this review, we summarize some extreme environmental factors used for the improvement of heterologo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 102 publications
1
20
0
Order By: Relevance
“…T7-SHuffle cells thus enable the oxidative folding of multi-disulfide bonds, and DsbC isomerase can potentially reshuffle non-native SS bonds [ 26 ]. Further, lowering the expression temperature to 16 °C slows down protein expression and stabilizes the native structure, thereby aiding the folding process [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…T7-SHuffle cells thus enable the oxidative folding of multi-disulfide bonds, and DsbC isomerase can potentially reshuffle non-native SS bonds [ 26 ]. Further, lowering the expression temperature to 16 °C slows down protein expression and stabilizes the native structure, thereby aiding the folding process [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning bioprocess optimization, the operational mode is a key factor in bioprocess design, batch or fedbatch being the most established modes for production at an industrial scale, while chemostat is more commonly used for strain characterization and bioprocess design (Looser et al, 2014;Kumar et al, 2020;Nieto-Taype et al, 2020a). Additionally, the application of different types of cell stress has been demonstrated to have a significant positive effect on RPP, so the established process strategies can be remarkably improved (García-Ortega et al, 2019;Chen et al, 2021). Some examples are the application of substrate starving periods (Garcia-Ortega et al, 2016;Çalık et al, 2018) and the implementation of oxygen limiting conditions (Baumann et al, 2008), which have shown a positive effect on RPP under P GAP regulation.…”
Section: Introductionmentioning
confidence: 99%
“… 2003 , Chen et al . 2021 ). On the other hand, the deletion of PTC1 reduces the cell wall β-1,6-glucan levels by activating Exg1p (Jiang et al .…”
Section: Resultsmentioning
confidence: 99%